Catch rates sourced from popular media: 1900-1998 - Ruth Thurstan; Edward T Game; John M Pandolfi (PANGAEA, 2017)
The data presented are sourced from popular media records of recreational fishing for the Noosa Estuary in southeast Queensland, Australia. The information contained in these articles includes species composition of recreational catches, and three distinct time series of catch and effort (n fish fisher-1 trip-1): recreational fishing trips, mean and best club competition results.